O trabalho remoto e os desafios dos gestores - Patini, Aline de Campos Gonçalves (2011)
This research tried to understand what the managers challanges of remote workers are. Today, the organizations are in an environment where global transformations occur with great speed due to the industrial revolutions, and especially the technological advances. Such transformations bring several changes to the work, which adhering the flexibility brings alternatives as: home office, the shared centers, the satellite centers, autonomous or outsourced employees etc. In this situation it s possible to find managers who need to work with remote employees. Considering the management processes, such as the selection and training, control of goals achieving, performance appraisal, motivation and plans for title and salary, this scenario brings many challenges to the managers. The base of a relationship between managers and employees is the communication, that is vital to the manager evaluate the employees performance, provide feedback and to outline strategies for professional development of both, himself and the teleworkers. Although the remote working presents great challenges, and that somehow can result in problems for workers, such as reducing workers' rights won during the twentieth century, it also offers benefits to the workers, managers and also for organizations. For the organization, may be the reduction of infrastructure cost, or increased penetration into international markets, allowing greater control and knowledge of local culture. Managers can work through the remote, have a more mature team with more knowledge about the activities carried on, able to self-manage and identify priorities. In your turn, remote workers expand knowledge, improve their skills and their quality of life. Finally, remote working can bring challenges, but also benefits for the organizations, managers, workers and society in general